A Survey of Bovine Mummified Foetus and Foetal Wastage at Bodija Abattoir in Ibadan Nigeria - Ogunbodede, M.A.; Oladele, G.M.; Akanbi, I.M. (Pakistan Journal of Nutrition, 2015)
A survey was carried out to determine the incidence of bovine mummified foetus and foetal wastage at Bodija central abattoir Ibadan from the slaughtered pregnant cows. During the survey, a total of 391,440 heads of cattle were slaughtered within January 2012 to December 2014 and 156,576 which represent 40% were cow. A total of 156,576 uteri were examined and 58,528 representing 35% were gravid uteri. It was discovered that a large number of slaughtered cows in this abattoir were pregnant and mummified foetus were discovered in some of them; this gave the opportunity to investigate the incidence of mummified foetus among the pregnant cows and to determine the amount of foetal wastage. The result shows 58,528 foetal wastage out of which 1332 which represent 2.28% were mummified foetus. It was concluded that more stringent measures should be taken against the butchers slaughtering pregnant cows and selling out of the productive groups of cows to the butchers should be discouraged. Government should come to the aid of the livestock farmers financially in order to reduce the economic loss been faced by the farmers through their selling out of the productive cows. Also, causal agents of the mummified foetus should be promptly eradicated.